Hubungan Persepsi Siswa Mengenai Iklim Kelas dengan Orientasi Tujuan Siswa dengan Mengontrol Self-Efficacy (Penelitian pada Siswa SMP Madania Bogor) - Suprayogi, M. Nanang (Bina Nusantara University, 2010)
This research is to test variable relations of student’s perception about class climate with student orientation variables to be self-efficacy variable as a controller variable. There are four types of purpose orientation, that are task orientation, self-enhancing ego orientation, self-defeating ego orientation, and work avoidance orientation. Each purpose orientation will direct students into specific learning behavior that will determine their learning result. The subjects of this research will be students in SMP Madania Bogor. This research uses calculation of partial correlation, double regression, and t-test.